Economic Analysis Relationship in Determining The Size of Parliamentary Threshold in Indonesia - Sholahuddin Al-Fatih (Universitas Muhammadiyah Tangerang, 2020)
This research tries to discuss the relationship of economic factors in the establishment of a legal norm. Through conceptual and statutory approaches, this study tries to examine the concept of the relationship between economics and the law initiated by Richard A. Posner. This research makes the establishment of the norm on the size of the parliamentary threshold in the implementation of legislative elections as a benchmark for the relationship between the economy and the law. The results of this study show that changes in the size of the parliamentary threshold can be understood as an open legal policy agreed upon by lawmakers. The existence of rules on open legal policy makes economic and legal relations in determining the norms of parliamentary threshold size become real. This research is expected to help academics and legal practitioners to dig deeper into the relationship between economics and law, so as to understand the advantages and disadvantages that may result from such relationships.